Effect of DGAT1 Gene on Hot and Cold Carcass, Neck and Non-Carcass Traits in Indonesia Sheep - F. Amri; A. Gunawan; C. Sumantri (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2023)
Quality carcass and non-carcass are two inseparable components that result from slaughtering animals with high economic value. The aims study is effect of polimorfisme DGAT1 gene on hot and cold carcass, neck and non-carcass traits in Indonesia sheep. A total of 50 rams used in this study were collected from 10 Barbados Cross Sheep (BCS), 10 Compass Agrinac Sheep (CAS), 15 Javanese Thin-Tailed Sheep (JTTS), and 15 Jonggol Sheep (JS). The sheep were slaughtered at 10-12 months old with an average body weight of 20.45 kg. Identification of the DGAT1 gene polymorphism was performed by Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP). The effect of the DGAT1 gene and breed with carcass and non-carcass traits were described using a T-test. The result showed that we found two genotypes: CC (466 bp), and CT (76, 390, and 466 bp) in sheep. The DGAT1 gene polymorphisms (g.8539 C>T) were in Hardy-Weinberg Equilibrium (HWE). The DGAT1 gene polymorphisms had a significant (P<0.05) on carcass traits in neck. However, the DGAT1 gene had no significant association (P>0.05) with non-carcass traits. The CT genotype had the highest value of carcass traits compared to CC genotypes. Therefore, the quality of carcass and non-carcass in Indonesian sheep for the DGAT1 gene only affects the neck value.